Foreign direct investment and the single market - J. Peter Neary (University College Dublin, Department of Economics, 2002)
This paper extends the theory of multinational corporations, identifying three distinct influences of internal trade liberalisation by a group of countries on the level and pattern of inward foreign direct investment (FDI). First, the tariff-jumping motive encourages plant consolidation. Second, the export platform motive favours FDI with only a single union plant relative to exporting, and may induce a firm which has never exported to invest. Finally, reduced internal tariffs increase competition from domestic firms, which dilutes the other motives and may induce a Fortress Europe outcome of multinationals leaving union markets even though external tariffs are unchanged.
hdl:10197/1319
Keywords: 330; Foreign direct investment; market integration; multinational corporations; Single Market; Direktinvestition; Wirtschaftsunion; Außenhandelsliberalisierung; Theorie; EU-Staaten